Physical and Mechanical Properties Exhauster Powder Generated in the Foundry Process for a New Ceramic Material considering the ISO 10545-1:2014 and 13006:2012 - Valentina, Luiz Oliveira Veriano Dalla; Folguera, Marilena Valadares; Knop, Wanessa Rejane; Prates, Glaucia Aparecida [UNESP] (My University, 2016)
This study aims to evaluate the potential use of exhauster powder generated in the foundry process as subproduct for a new product development. Formulations were prepared with different exhauster powder content. The sintered materials at 1000, 1100 and 1200°C were characterized according technological properties as water absorption, linear shrinkage and apparent density. Microstructural analysis was carried out by scanning electron microscopy. It was observed that the waste increase the density in sintering process and with high levels of waste occurs an increase of the porosity and intensification in the color of the new material. The formulations prepared with different exhauster powder content and this new material were characterization by thermal analysis (ATD, TG), and some technological properties such as water absorption, linear shrinkage, apparent density. Finally, were tested for resistance to bending, abrasion and the morphological analysis. The results showed the new material can be used as ceramic tiles, for, in general no significant changes it's physical and mechanical properties considering both ISO 10545-1:2014 and 13006:2012.
Keywords: Exhauster powder; Industrial wastes; Material ceramics